Complexity of near-surface deformation and subsurface structure of the Chihshang creeping fault-line scarp, eastern Taiwan: insights from integration of geological and geophysical data - W. J. Huang; M. T. Fitrianto; C. C. Chen; P. Y. Chang; I. C. Yen; M. Le Béon; S. T. Lu (Earth, Planets and Space)
Abstract The precise position and geometry of a fault and the recognition of contemporary active strands are pivotal elements for formulating regulations for earthquake fault zones and fault setbacks. The western frontal escarpment toe of the Coastal Range in Tapo, eastern Taiwan is commonly considered as the plausible location of the N18°E-trending, east-dipping Chihshang creeping seismogenic fault. Frontal collapse and flattening of reverse faulting, in addition to fluviation and landslide have complicated the process for defining the Chihshang fault configuration. We used a multidisciplinary approach, combining site investigation, geological core analysis and correlation, resistivity prospecting, and inclinometer monitoring, to illuminate the subsurface structure and deformation of the leading edge of the Chihshang fault at Tapo Elementary School. We found that (1) the Chihshang main fault is a contact of alluvium deposits and the mudstone of Lichi mélange, and has a dip angle of approximately 77° within the resistivity gradation zone 55 m east of the toe of the geomorphic escarpment; (2) it has a 2-year cumulative horizontal displacement of 20.7 mm northwestward and continuously creeps without seasonal variation; and (3) the active deformation on the escarpment results from a combined effect of fault creeping and slow gravity sliding of the mass which is steadily supplied by the Chihshang reserve faulting. A mechanism of faulting-relay landsliding is proposed to understand the active deformation on the escarpment. Great caution is needed in the interpretation of the aseismic surface ruptures along the inferred trace of reverse creeping faults as fault branching. Graphical Abstract